Informality: does financial development matter?. Issue 1 (14th March 2017) - Sirisankanan, Aeggarchat
Abstract : Purpose: Financial development may be an alternative policy for controlling informal employment. However, there is still an ambiguous relationship between financial development and informal employment. The purpose of this paper is to examine the impact of financial development on informal employment. Design/methodology/approach: The paper is based on both the occupational choice model and on the concept of financial development and economic growth which can produce either a positive or negative relationship between financial development and informal employment. Consequently, the author formulated empirical specifications and applied an econometric technique to examine the actual relationship. Findings: The empirical results indicated that financial development can reduce informal employment. The author also found that the relationship between financial development and informal employment varies, depending on the level of economic growth and development. Research limitations/implications: Even though there are many types of informal employment, this paper uses only informal self-employment as a proxy of informal employment. To implement it properly, all types of informal employment should also be examined. Practical implications: Becoming informal employment depends on several factors; policy makers for each country should carefully examine the specific relationship between financial development and informal employment for their own country. Social implications: The paper presents alternative choices for policy makers to control informal employment by increasing financial development, especially in developing countries. This policy also includes promoting microfinance which will contribute to both formality and increasing the strength of the community. Originality/value: From the two possible impacts of financial development on informal employment, this paper affirms that financial development can reduce informal employment.